2015
DOI: 10.1371/journal.pone.0118748
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Chronic Sublethal Effects of Imidacloprid on Honey Bee Colony Health

Abstract: Here we present results of a three-year study to determine the fate of imidacloprid residues in hive matrices and to assess chronic sublethal effects on whole honey bee colonies fed supplemental pollen diet containing imidacloprid at 5, 20 and 100 μg/kg over multiple brood cycles. Various endpoints of colony performance and foraging behavior were measured during and after exposure, including winter survival. Imidacloprid residues became diluted or non-detectable within colonies due to the processing of beebrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
2
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 71 publications
12
150
2
8
Order By: Relevance
“…Although numerous studies report effects of neonicotinoids on foraging behavior in bees, some contradictory evidence following exposure to the neonicotinoids also has been reported (Dively et al, 2015;Franklin et al, 2004;Pilling et al, 2013). Some of these studies examined the effects on foraging after exposure to seed-treated crops; however, Dively et al (2015) fed 10 replicate colonies 0, 2, 20, or 100 μg/kg imidacloprid over a 12-week period, reporting no adverse effects on foraging activity as measured by the number of foragers returning to the hive or the number of animals loaded with pollen pellets.…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies report effects of neonicotinoids on foraging behavior in bees, some contradictory evidence following exposure to the neonicotinoids also has been reported (Dively et al, 2015;Franklin et al, 2004;Pilling et al, 2013). Some of these studies examined the effects on foraging after exposure to seed-treated crops; however, Dively et al (2015) fed 10 replicate colonies 0, 2, 20, or 100 μg/kg imidacloprid over a 12-week period, reporting no adverse effects on foraging activity as measured by the number of foragers returning to the hive or the number of animals loaded with pollen pellets.…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%
“…Some of these studies examined the effects on foraging after exposure to seed-treated crops; however, Dively et al (2015) fed 10 replicate colonies 0, 2, 20, or 100 μg/kg imidacloprid over a 12-week period, reporting no adverse effects on foraging activity as measured by the number of foragers returning to the hive or the number of animals loaded with pollen pellets. Nevertheless, this study noted a 12% decrease in foraging activity compared to control during late August and early September, observations collected after the pesticide exposure period (Dively et al, 2015).…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%
“…Vários estudos têm mostrado que uma ampla gama de agrotóxicos pode ser encontrada nas colônias e que estes compostos podem interagir com agentes patogênicos (Pettis et al 2013). Efeitos de inseticidas sobre as rainhas foram documentados, mas o efeito em toda a colônia muitas vezes não é observado de forma significativa (Sandrock et al, 2014;Dively et al, 2015). Outros estudos de campo foram realizados, mas os resultados ainda são controversos (Pilling et al, 2013;Cutler et al, 2014;Rundlöf et al, 2015).…”
Section: Histórico Da Síndrome "Distúrbio Do Colapso Das Colônias" Nounclassified
“…Em estudos de campo, realizados com tiametoxam por Pilling et al (2013) e com clotianidina por Cutler et al (2014), ambos no tratamento de sementes e com as doses recomendadas, nenhum efeito adverso foi observado sobre as abelhas campeiras. No entanto, Dively et al (2015) encontraram alterações significativas na taxa de sobrevivência das abelhas expostas às doses de 20 e 100 µg kg -1 de imidacloprido, em comparação ao grupo-controle, durante três anos. Porém, a dose de 5 µg kg -1 -dose residual encontrada nas matrizes vegetais, como pólen e néctar em girassol (Schmuck et al, 2001), e em coletas em diferentes culturas (Bonmatin et al, 2003) -, não causou alterações de comportamento de forrageamento e da taxa de sobrevivência.…”
Section: O Uso De Agrotóxicos Na Agriculturaunclassified
“…In March, Goulson reanalysed 3 data from a 2013 study by the UK Food and Environment Research Agency (see go.nature.com/w9jlti), which had concluded that neonicotinoid pesticides do not harm bees: Goulson found that they do. In the same month, work from the United States found 4 that the probable harm from exposure to imidacloprid in seed-treated crops was "negligible" in honeybees, and last year a study 5 done in Canada reached a similar conclusion for clothianidin on oilseed rape.…”
mentioning
confidence: 96%